Effect of Surgical Masks on Cardiopulmonary Function in Healthy Young Subjects: A Crossover Study - Zhang, Guolin; Li, Mei; Zheng, Meifeng; Cai, Xiaoqing; Yang, Jinyu; Zhang, Shengqing; Yilifate, Anniwaer; Zheng, Yuxin; Lin, Qiang; Liang, Junjie; Guo, Lan; Ou, Haining (Frontiers in Physiology, 2021)
Objective: Masks play an important role in preventing infectious respiratory diseases. The influence of wearing a mask for physical exercise on the human body needs to be studied. The purpose of this study is to explore the influence of wearing surgical masks on the cardiopulmonary function of healthy people during exercise. Methods: The physiological responses of 71 healthy volunteers (35 males and 36 females, age 7.77 ± 7.76 years) wearing surgical masks and not wearing masks were analyzed. Cardiopulmonary function and metabolic reaction were measured by CPET. All tests were carried out in random sequence and should be completed within 1 week. Results: The CPET with mask-on condition performed worse than the mask-off condition (P＜0.05): the Borg scale was higher (P<0.001). The VO2/kg was lower than the mask-off before exercise (P＜0.05), and it was more obvious at the peak of exercise (VO2/kg: 24.33 ± 4.96 vs. 27.3 ± 5.47 ml/min/kg, P<0.001), and the anaerobic threshold brought forward (P<0.001). The Rf and VE values – reflecting pulmonary ventilation function – were lower during mask-on than those during mask-off in CPET, especially during peak exercise (RF: 33.8 ± 7.98 vs. 37.91 ± 6.72b/min, P＜0.001; VE: 55.07 ± 17.28 vs. 66.46 ± 17.93 L/min, P<0.001). VT was significantly lower than mask-off at the peak of exercise (1.66 ± 0.45 vs. 1.79 ± 0.5 L, P<0.001). PETO2, PETCO2, VE/VO2, and VE/VCO2, which reflect the pulmonary ventilation efficiency, were significantly different in different stages of CPET (P<0.05), but there was no significant difference in SPO2 between them. The mask-on condition was lower than mask-off in VO2/HR, SV, OUES, △VO2/△W, and peak HR in each stage of CPET (P<0.05), but only systolic blood pressure was significantly different at the peak of exercise (P<0.05). Conclusion: Wearing surgical masks affects the pulmonary ventilation function, ventilation efficiency, and exercise endurance of healthy people and influences cardiovascular function. For patients with cardiopulmonary diseases, the above physiological changes might aggravate the patient’s condition, so it is necessary to exercise care when wearing masks.